2021
DOI: 10.1186/s12891-021-04417-z
|View full text |Cite
|
Sign up to set email alerts
|

The deep vein thrombosis of lower limb after total hip arthroplasty: what should we care

Abstract: Background Deep vein thrombosis (DVT) of lower limb is one of the common complications after total hip arthroplasty(THA), we aimed to evaluate the potential risk factors of DVT of lower limb in patients with THA, to provide insights into the management of THA. Methods Patients who underwent THA in our hospital from January 1, 2017 to November 30, 2020 were included. The personal characteristics and clinical data of DVT and no-DVT patients were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…Current literature lacks consensus regarding the most appropriate VTE prophylactic agent for patients undergoing simultaneous bilateral joint replacements. Previous studies comparing different agents examined heterogenous cohorts containing both unilateral and bilateral THA 232-234 . In addition, another study compared the efficacy of aspirin with that of other anticoagulants only after risk-stratifying unilateral cases into a “low-risk” group that received aspirin, and bilateral cases into a “high-risk” group that received potent anticoagulants, thus making it difficult to make a valid comparison 235 .…”
Section: - What Is the Chemoprophylactic Agent Of Choice For Patients...mentioning
confidence: 99%
“…Current literature lacks consensus regarding the most appropriate VTE prophylactic agent for patients undergoing simultaneous bilateral joint replacements. Previous studies comparing different agents examined heterogenous cohorts containing both unilateral and bilateral THA 232-234 . In addition, another study compared the efficacy of aspirin with that of other anticoagulants only after risk-stratifying unilateral cases into a “low-risk” group that received aspirin, and bilateral cases into a “high-risk” group that received potent anticoagulants, thus making it difficult to make a valid comparison 235 .…”
Section: - What Is the Chemoprophylactic Agent Of Choice For Patients...mentioning
confidence: 99%
“…Femur fractures are a common type of fracture in the elderly and the etiology mainly includes external force hitting, high fall injury, and traffic accidents [8,9] . Hip arthroplasty is an effective means of clinical treatment of femur fracture and its efficacy is relatively precise, but there is a risk of postoperative lower extremity deep vein thrombosis and other complications, and it is necessary to cooperate with corresponding postoperative care measures, so as to promote its postoperative rehabilitation [10,11] . Previous clinical treatment for elderly patients undergoing hip arthroplasty with femoral fracture takes the way of routine nursing mostly, the nursing measures used were relatively single, the nursing content was not abundant enough, and they failed to differ according to the rehabilitation characteristics of patients at different stages of postoperative care, nursing care was not very specific, and the nursing effect was not ideal.…”
Section: Resultsmentioning
confidence: 99%
“…These findings may suggest a shift in surgical candidate selection during the COVID-19 pandemic to mitigate the risks posed by prior DVT. [ 29 ] Previous studies have demonstrated that patients with a history of DVT who undergo lower limb joint arthroplasty have a higher incidence of DVT during the 90 day post-op period than those with no history of DVT [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%